Current status of Euphylliidae corals in marine protected areas of Tioman, Redang and Payar Islands, Malaysia - Saad, Shahbudin; Khodzori, Mohd Fikri Akmal; Ku Sulong, Ku Abdullah 'Ulwan; Md Zain, Khairul Amira (2016)
Recently, various conservation efforts of the Euphylliidae corals have been taken placed since these species are heavily targeted for the marine aquarium trade. In Malaysia, the information coverage, distribution and abundance patterns of these vulnerable and near threatened species are not fully documented. Hence, the current status of the Euphylliidae corals were investigated by applying a method of coral video transect at 144 transect lines in 36 reef sites of Tioman, Redang and Payar Islands. This study recorded a total of six species of the Euphylliidae corals with Euphyllia ancora had the highest average percentage coverage (29.5% ± 1.5) and dominant in Tioman, Plerogyra sinuosa (92.3% ± 4.2) in Redang and Physogyra lichtensteini (98.0% ± 6.7) in Payar Islands. The diversity and distribution of the Euphyllidae corals were highly influenced by the difference in reef morphology, substrate condition, coastal development and human intervention at the particular reef area.